SURVEY OF ANTI-THYROGLOBULIN CONCENTRATION IN PATIENTS WITH PAPILLARY THYROID CARCINOMA AFTER TOTAL THYROIDECTOMY (DA NANG JOURNAL OF MEDICINE AND PHARMACY, 2026)
Objectives: This study aims to evaluate the value of Anti-Thyroglobulin (TgAb) levels after total thyroidectomy and examine the relationship between serum TgAb levels and thyroid cancer stages in patients with papillary thyroid carcinoma (PTC). Methods: Retrospective study of 160 papillary thyroid cancer patients after total thyroidectomy from 01/2023 to 07/2024 at Cho Ray Hospital. Results: The median TgAb level decreased significantly (p
Keywords: papillary thyroid carcinoma; anti thyroglobulin; total thyroidectomy